Fitoremediasi Menggunakan Variasi Kombinasi Tanaman Kiambang (Salvinia molesta M) dan Tanaman Kayu Apu (Pistia stratiotes L) dalam Menurunkan Besi (Fe) dengan Sistem Batch - Maryana Maryana; Sarita Oktorina; Shinfi Wazna Auvaria; Rr diah Nugraheni Setyowati (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2020)
The increased industrial development can cause pollution and environmental damage. Iron metal (Fe) is an essential metal whose existence is a certain amount needed by living organisms, but in excessive amounts will cause toxic effects. To overcome this problem, an environmentally friendly technology is needed, namely phytoremediation technology using kiambang plants (Salvinia molesta M) and Kayu apu plants (Pistia stratiotes L). The purpose of this study was to determine the efficiency of reducing the concentration of iron (Fe) in ground water using a combination of kiambang (Salvinia molesta M) and a combination of Kayu apu plants (Pistia stratiotes L). This research method is experimental and the research approach used is qualitative analysis. The process of phytoremediation with a batch system using a Kiambang plant (Salvinia molesta M) and wooden apu (Pistia stratiotes L) as much as 300 grams (uses a variation of the amount different from the same weight (25:75) (150:150) (75:25)) in each reactor. The results showed a decline on the 12th day. In the reactor treatment group of 1 is 0.30 mg/l and efficiency at 47%, reactor 2 is 0.06 mg/l and efficiency of 93%, and reactor 3 is 0.49 mg/l and efficiency of 9%. The highest efficiency value in decreasing the concentration of iron (Fe) in groundwater using variations in the combination of Kiambang plant (Salvinia molesta M) and the wooded plant (Pistia stratiotes L) in the reactor treatment group 2 is 93% on the 12th day.